A Cultural Critique of Chinua Achebe’s Book “Things Fall Apart”: The Igbo Ethnic Group’s Excessive Desire for Materialism - Nyeenenwa , Stephen (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2022)
This work is an attempt to review one of the masterpieces of African literature, Chinua Achebe’s Things Fall Apart. From an African perspective, I will rely on cultural criticism to offer a conventional interdisciplinary enquiry into the work that has been widely acclaimed as a classic. I will then proceed to deconstruct them in such a way that it will give a guide on what the interplays were that acted on the prime character, Okonkwo; how the societal values, in this case, achievement, wealth, and materialism, acted as catalysts and baits that drew him to his tragic end. I will not fail to reflect on how the Umuofia society in which he lived in Things Fall Apart was organised and how it reflects the ideals upon which Igbo society generally is built and the values they hold dear. This allows me to gain some insight into the social, political, psychological, and historical conflict, dissent, and contradictions that influenced Okonkwo by providing these structures of meaning with relevant assumptions that have objective representations. I discovered that the invasion and forceful change of the cultural perspective of Chinua Achebe’s Umuofia came to light because the colonialists had also brought a government and a system of running it; schools, trading, and government reinforced each other and combined to undo the old order. I further argued that Okonkwo’s excessive quest for wealth reflects ills from the Igbo culture, which has ultimately extended to all of Nigeria in recent times.